Karakterisasi komponen gizi kacang gude (Cajanus cajan) berdasarkan variasi metode preparasinya: Characterization of the nutritional components of pigeon peas (Cajanus cajan) based on variations in preparation methods - Irwan; Putri, Ariella Ramadhani; Utami, Sri Wira (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2024)
Pigeon pea (Cajanus cajan) is one type of legume that is not yet popular in Indonesia, especially in South Sulawesi. Despite its high nutritional content, pigeon pea contains an anti-nutritional compound called phytic acid, which can inhibit nutrient absorption. This study aims to determine the effect of soaking, boiling, and fermentation on the reduction of phytic acid levels and the nutritional characteristics of pigeon pea. The research was conducted in two stages: the first stage to examine the effect of treatments on the reduction of phytic acid, and the second stage to characterize the nutritional components of pigeon pea flour after the best treatment was obtained. The results showed that 48-hour fermentation resulted in the highest reduction of phytic acid levels at 72.01%, while 24-hour soaking resulted in the lowest reduction at 53.705%. Nutritional characterization in the second stage showed that fermented pigeon pea had a moisture content of 7.53%, ash content of 2.56%, protein content of 20.61%, fat content of 0.80%, and carbohydrate content of 68.51%. In conclusion, 48-hour fermentation is the best treatment to reduce phytic acid levels in pigeon pea, with a reduction of 72.01%